Effective (Pd, Ni)Sn4 diffusion barrier to suppress brittle fracture at Sn-58Bi-xAg solder joint with Ni(P)/Pd(P)/Au metallization pad. (February 2022) - Kim, Jungsoo; Park, Dae-Young; Ahn, Byeongjin; Bang, Junghwan; Kim, Min-Su; Park, Hyun-Soon; Sohn, Yoonchul; Ko, Yong-Ho
Abstract: In this study, we investigated the interfacial reactions and mechanical properties of Sn58Bi solders alloyed with Ag nanoparticles (NPs) after bonding with electroless nickel-immersion gold (ENIG) or electroless nickel-electroless palladium-immersion gold (ENEPIG) surface finish. On the ENIG surface finish, Ni3 Sn4, Ni-Sn-P, and Ni3 P layers were sequentially formed on the Ni(P) layer. On the ENEPIG surface finish, (Pd, Ni)Sn4 intermetallic compound was formed on thin Ni3 Sn4 /Ni3 P on the Ni(P) layer, and it survived nine reflow cycles, unlike Sn-Ag-Cu solder joints in previous studies. This effectively stopped the formation of the Ni-Sn-P layer, which acted as an effective diffusion barrier to suppress the consumption of Ni in the Ni(P) layer. A mixed-mode fracture—partially through the bulk solder (ductile mode) and partially through Kirkendall voids in the Ni-Sn-P layer (brittle mode)—was observed with the Sn-58Bi-xAg/ENIG joint, whereas only ductile fracture was observed with the Sn-58Bi-xAg/ENEPIG joint. Alloying with 0.5 wt% Ag NPs strengthened the composite solder by refining the eutectic microstructure of the Sn58Bi solder and by inducing precipitation hardening with fine Ag3 Sn particles. However, the addition of more Ag NPs led to mechanical degradation by re-coarsening of the eutectic microstructure and by providing an easy fracture path along the coarsened Ag3 Sn/solder interface. The highest shear strength was obtained with Sn-58Bi-0.5Ag/ENEPIG, which was suggested to be the most reliable system for low-temperature soldering at 200 °C. Highlights: Interfacial reactions of Sn58Bi solders alloyed with Ag NPs were investigated with ENIG and ENEPIG surface finishes. The (Pd, Ni)Sn4 intermetallic compound formed over the Ni3 Sn4 /Ni3 P layer survived nine reflow processes. The (Pd, Ni)Sn4 acted as an effective diffusion barrier to suppress consumption of Ni in the Ni(P) layer. A mixed-mode fracture was observed with ENIG, while only ductile fracture was with ENEPIG surface finish. The highest shear strength was obtained with Sn-58Bi-0.5Ag/ENEPIG solder joint.